Evaluation of exo-long noncoding RNA MALAT1 in OSCC in comparison to dysplastic and normal: A cross-sectional study - Ramya Sekar; Selvaraj Jayaraman; VishnuPriya Veeraraghavan; Kalaiselvi Krishnamoorthy; Shubhra Chauhan Aramanai; Sathan Raj Natarajan (Journal of Oral Biology and Craniofacial Research)
Objective: This study explores the role of MALAT1 as a valuable target for creating minimally-invasive diagnostic methods and personalized treatments in the management of OSCC. It focuses on evaluating the role of exosomal MALAT1 in the progression of dysplasia to OSCC by influencing the PI3K/AKT pathway. Method: This cross-sectional study evaluated MALAT1 expression and PI3K/AKT pathway components in exosomes derived from plasma samples of patients with various stages of oral dysplasia, OSCC and compared with normal. RNA concentration was estimated, real-time polymerase chain reaction (qPCR) was used for quantitative analysis. Gene expression levels of MALAT1, PI3K, AKT1, and PTEN were analysed and compared across groups using one way ANOVA and Post-hoc Tukey analysis was performed for pairwise comparisons to assess correlations between MALAT1 expression and PI3K/AKT pathway components. Result: MALAT1 was found to be overexpressed in OSCC in comparison to normal, significantly (p < 0.001∗). There was no significant change in expression pattern of MALAT1 between dysplastic patients and normal, yet, significant association was found on corelation analysis between expression pattern of MALAT1 and PI3K/AKT/PTEN (p 0.001∗) among individuals of dysplasia and OSCC. As well pairwise comparisons of MALAT1 expression levels between all three stages of dysplasia showed significant association (p < 0.001∗). Conclusion: MALAT1 stands out as a key player in the complex landscape of OSCC pathogenesis, impacting tumorigenesis, metastasis, and treatment outcomes through multifaceted molecular mechanisms. Continued research into MALAT1's regulatory roles and its interactions within the tumor microenvironment holds promise for uncovering novel therapeutic targets and biomarkers that could redefine the management of OSCC in the future.